Peran efikasi diri dan dukungan sosial terhadap quarter life crisis pada anak sulung di Bali - Anjani, I Gusti Mutiara Dewita; Swandi, Ni Luh Indah Desira (Jurnal Psikologi Ulayat, 2026)
Eldest children in early adulthood face unique challenges during the quarter life crisis, particularly in Bali, where they bear the responsibility of upholding family traditions, generating income, and serving as role models. These pressures can lead to internal struggles such as self-efficacy issues and external stress arising from social expectations. This study explored how self-efficacy and social support contribute to the quarter life crisis among eldest children in Bali. Using quantitative methods and data from 110 participants, the study found that self-efficacy and social support together explained 55.8% of the variance in quarter life crisis experiences. The results suggest that strengthening self-efficacy and enhancing social support may help mitigate the challenges associated with the quarter life crisis. This research may inform future interventions aimed at supporting eldest children during this critical life phase.